Commonshare: A New Approach to Social Reputation for Online Collaborative Communities - Rough, Daniel; De Paoli, Stefano; Wilson, Anna (Social Science Computer Review)
Reputation systems are a popular feature of web-based platforms for ensuring that their users abide by platform rules and regulations and are incentivized to demonstrate honest, trustworthy conduct. Accrual of "reputation" in these platforms, most prominently those in the e-commerce domain, is motivated by self-interested goals such as acquiring an advantage over competing platform users. Therefore, in community-oriented platforms, where the goals are to foster collaboration and cooperation among community members, such reputation systems are inappropriate and indeed contrary to the intended ethos of the community and actions of its members. In this article, we argue for a new form of reputation system that encourages cooperation rather than competition, derived from conceptualizing platform communities as a networked assemblage of users and their created content. In doing so, we use techniques from social network analysis to conceive a form of reputation that represents members' community involvement over a period of time rather than a sum of direct ratings from other members. We describe the design and implementation of our reputation system prototype called "commonshare" and preliminary results of its use within a Digital Social Innovation platform. Further, we discuss its potential to generate insight into other networked communities for their administrators and encourage cooperation between their users.
Keywords: Digital; Réservé UdeM

Commonshare: A New Approach to Social Reputation for Online Collaborative Communities - Rough, Daniel; De Paoli, Stefano; Wilson, Anna (Social Science Computer Review, 2021)
Reputation systems are a popular feature of web-based platforms for ensuring that their users abide by platform rules and regulations and are incentivized to demonstrate honest, trustworthy conduct. Accrual of "reputation" in these platforms, most prominently those in the e-commerce domain, is motivated by self-interested goals such as acquiring an advantage over competing platform users. Therefore, in community-oriented platforms, where the goals are to foster collaboration and cooperation among community members, such reputation systems are inappropriate and indeed contrary to the intended ethos of the community and actions of its members. In this article, we argue for a new form of reputation system that encourages cooperation rather than competition, derived from conceptualizing platform communities as a networked assemblage of users and their created content. In doing so, we use techniques from social network analysis to conceive a form of reputation that represents members' community involvement over a period of time rather than a sum of direct ratings from other members. We describe the design and implementation of our reputation system prototype called "commonshare" and preliminary results of its use within a Digital Social Innovation platform. Further, we discuss its potential to generate insight into other networked communities for their administrators and encourage cooperation between their users.
Keywords: Digital; Réservé UdeM